Study on Occupational Radiation Exposure at Different Hospitals in Nepal using ThermoluminescenceDosimetry - Acharya, Prabhash; Chalise, Gita; Rijal, Bipin; Lamichhane, Hari Prasad; Shah, Buddha Ram (Nepal Journal of Science and Technology, 2020)
The clinical efficacy of using ionizing radiation in diagnosis and treatment of diseases has been revolutionized, benefitting humankind and, at the same time, imposing deleterious health effects, if not handled carefully. Personnel dosimetry has emerged as an essential tool to monitor occupational radiation exposure. The present study intends to reveal and describe the scenario of occupationally exposed staff by assessing an individual’sdose in radiological facilities at different hospitals in Nepal. Thermoluminescent Dosimetry (TLD) has been used for assessing individual doses. Altogether eight hospitals were chosen from different locations of Nepal. TLD badges were worn by the radiation workers on their chest level while working with the radiological equipment for about three to ten months during their routine work. Later the badges were read out in the TLD badge reader system available at Nepal Academy of Science and Technology (NAST) to obtain the exposed doses. CaSO4: Dy was used as TL phosphor. Exposed doses for health personnel during their routine work were foundin the range of (2.21 to 16.17) 0.01 mSv per year, which was low compared to the permissible dose limit of 20 mSv per year set up by International Commission on Radiological Protection(ICRP). Although the exposed dose rates in the monitored hospitals are below the recommended dose limits, it should be made as low as possible based on the ALARA principle.